E-Business as a Catalyst in the Implementation of Sustainable Green Banking Practices - Amanda Ridho Ivanza (Journal of Management Economics and Financial Accounting, 2025)
The development of digital technology and the demand for more environmentally friendly banking practices increasingly demonstrate the importance of implementing the concept of green banking. On the other hand, e-business, which involves electronic transactions and the use of digital platforms to provide various services, acts as a catalyst in encouraging the implementation of sustainability principles in the banking sector. This article discusses how e-business can accelerate the adoption of green banking practices, as well as its implications for the banking industry and its impact on environmental sustainability. This study aims to analyze the role of e-business in introducing and implementing more efficient and environmentally friendly green banking practices.